Preservation of the infrapatellar fat pad during total knee arthroplasty reduces subacute postoperative anterior knee pain: a randomized controlled trial - Pruk Chaiyakit; Bunpreedee Petcharat; Ittiwat Onklin (BMC Musculoskeletal Disorders)
Abstract Background Preservation of the infrapatellar fat pad (IPFP) during total knee arthroplasty (TKA) is associated with a lower incidence of postoperative anterior knee pain (AKP). However, the comparative efficacy of IPFP preservation remains unclear. The objective of this randomized controlled trial (RCT) was to compare the incidence of AKP between IPFP preservation and partial excision of the IPFP. Methods This prospective RCT included patients with primary varus gonarthrosis < 20° who underwent unilateral computer-assisted TKA between March 2019 and November 2020. Patients were randomly assigned to the partial excision or preservation groups. The intraoperative and postoperative protocols were the same in each group. The incidence and severity of AKP, range of motion (ROM), and modified Western Ontario and McMaster Universities Arthritis Index (WOMAC) score were assessed at 1, 3, 6, and 12 months postoperatively and then annually thereafter. The pre- and postoperative Insall–Salvati ratio (ISR) and mechanical alignment (MA) were also evaluated. Results A total of 57 patients were included (27 in the partial excision group and 30 in the preservation group). At 1 month postoperatively, the preservation group had a significantly lower incidence of anterior knee pain (AKP) than the partial excision group (33.3% versus 77.8%, p = 0.001). The visual analogue scale (VAS) pain score was also significantly lower in the preservation group at 1 month (1.2 ± 2.0 vs. 2.4 ± 1.6, p < 0.05). However, these differences were not observed at later follow-up time points (3, 6, or 12 months). Modified WOMAC scores, range of motion (ROM), mechanical alignment (MA), and Insall–Salvati ratio (ISR) did not differ significantly between groups at any time point. Although a statistically significant difference in WOMAC score was observed at 6 months, the magnitude of this difference was below the minimal clinically important difference (MCID), indicating limited clinical relevance. Conclusion IPFP preservation during TKA reduced the incidence and severity of subacute postoperative AKP. Level of evidence: I. Trial registration Thai Clinical Trials Registry, TCTR20220215011 Registered 08/02/2022 - Retrospectively registered, https://www.thaiclinicaltrials.org/show/TCTR20220215011 .